2023
DOI: 10.1093/ejo/cjac073
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary dimensions and arch shape with palatally displaced canines

Abstract: Summary Background/objectives The aim of this study was to explore the effect of palatally displaced canines on maxillary dimensions and arch shape. Methods Occlusal and skeletal landmarks were plotted on cone beam computed tomography (CBCT) images of 156 orthodontic patients: 78 with palatally displaced canines (PDC) (27 left, 28 right, and 23 bilateral) and 78 controls using Mimics™ (Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
1
5
0
2
Order By: Relevance
“…Discriminant analysis also showed an accurate classification of 85.9% for the control group and 66.7% for the PDC group. In the present study, prediction accuracy was 70% for the control group and 68.9% for the PDC [ 29 ].…”
Section: Discussionmentioning
confidence: 85%
“…Discriminant analysis also showed an accurate classification of 85.9% for the control group and 66.7% for the PDC group. In the present study, prediction accuracy was 70% for the control group and 68.9% for the PDC [ 29 ].…”
Section: Discussionmentioning
confidence: 85%
“…The appropriate timing of the maxillary arch expansion procedure could resolve the transverse deficiency and lower the risk of canine impaction [ 28 ]. In contrast, Saade et al [ 29 ] found wider first molar and premolar widths in patients with palatally displaced canines. This might be due to the different methodologies applied.…”
Section: Discussionmentioning
confidence: 93%
“…Smatra se da se etiopatogeneza bukalnih (BI) i palatinalnih impakcija (PI) očnjaka suštinski razlikuje 6,7 . Bukalno impaktirani očnjaci češće se povezuju sa nedostatkom prostora u gornjoj vilici, sagitalnom i transveralnom nerazvijenošću maksile, teskobom i uskom apikalnom bazom 8 ; veći broj palatinalno impaktiranih očnjaka uočen je pak kod pacijenata sa dobro razvijenom gornjom vilicom, prerazvijenom apikalnom bazom, te pacijenata kod kojih nije prisutna teskobnost zubnih nizova 7,9,10 . Cilj rada bio je ispitati i analizirati kefalometrijske karakteristike pacijenata sa impaktiranim stalnim očnjakom.…”
Section: Uvodunclassified
“…Ukoliko se rizik od impakcije prepozna u ranoj fazi, primena interceptivnih mera, poput ekstrakcije mlečnog očnjaka 16,17 i upotrebe aparata za rapidnu ekspanziju palatuma 18 , može umnogome doprineti nicanju ovih zuba. Mnogi autori su pokušavali da ispitivanjem i analiziranjem dentoskeletnih karakteristika predvide rizik od nastanka impakcije maksilarnog očnjaka 1,6,8,19,20 . Kada je reč o sagitalnim parametarima, analiza ANB ugla sprovedena u okviru ove studije ukazala je na najveću zastupljenost impaktiranog očnjaka u grupi pacijenata II klase po Angleu (44,3%), dok je najmanji broj ispitanika u grupi pacijenata III klase po Angleu (25,7%).…”
Section: Diskusijaunclassified
See 1 more Smart Citation